Плоская задача о краевых эффектах в композите периодической структуры, армированном прямоугольными волокнами - Коханенко, Н.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The plane problem on the edge effects in a matrix composite of regular structure reinforced by rectangular fibers is considered in the exact statement. Components of a composite are linearly elastic and isotropic bodies. The composite is loaded by the uniaxial uniform load.
The criterion of estimate of the zones with edge effects is formulated. On a parameter of the composite structure, the problem of elasticity is formulated, and its solution is obtained by the variation-difference method.